2018
DOI: 10.3390/met8121036
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Post-Sintering Temperatures on the Microstructures and Mechanical Properties of a Pre-Sintered Co–Cr Alloy

Abstract: Although a cobalt–chromium (Co–Cr) blank in a pre-sintered state has been developed, there are few data on the optimal temperature for the alloy in terms of the desired mechanical properties. A metal block (Soft Metal, LHK, Chilgok, Korea) was milled to produce either disc-shaped or dumbbell-shaped specimens. All the milled specimens were post-sintered in a furnace at 1250, 1350 or 1450 °C. The microstructures, shrinkage and density of the three different alloys were investigated using the disc-shaped specimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The 3D printed specimen has a disadvantage in that the manufacturing cost is not economical and has a brittle property. However, this method has a fast production speed, less material waste, and a significantly lower incidence of porosity [ 6 , 7 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 3D printed specimen has a disadvantage in that the manufacturing cost is not economical and has a brittle property. However, this method has a fast production speed, less material waste, and a significantly lower incidence of porosity [ 6 , 7 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of sintering temperatures on the mechanical properties of a presintered Co-Cr alloy was examined, and the result indicated that over-sintering, about 1350℃, is better than under-sintering in terms of strength. It also showed that the number and size of the pores in the microstructure were largely related to the sintering temperature 26…”
Section: Discussionmentioning
confidence: 97%
“…A presintered soft block can be milled by dry machining with low contamination risk, which is an easier process than sintered Co-Cr milling [ 19 ]. The milled framework should be sintered in an argon atmosphere sintering oven at 1250-1400°C for 1 hour or 2 hours [ 20 , 21 ]. While there is no contraction shrinkage of a fully-sintered alloy used for hard milling, the shrinkage rate is 10-11% for soft-milled alloys after sintering [ 14 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…While there is no contraction shrinkage of a fully-sintered alloy used for hard milling, the shrinkage rate is 10-11% for soft-milled alloys after sintering [ 14 , 22 , 23 ]. The post-sintering after milling could affect the mechanical strength of soft-milled alloy [ 21 ], and 1350°C was reported to be the most suitable temperature [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%